An Analytical Study Of Short Stories Of Najamuddin Ahmed - Dr. Aasma Rani , Dr. Rashid Hameed , Dr. Syeda Attiya Khalid , Dr. Mutahir Shah , Sajid Iqbal , Dr. Musarrat Khan (Migration Letters, 2024)
Najamuddin Ahmed belongs to Bahawalnagar. He was born on 2 June 1971 in Bahawalnagar and studied there. He has done MA in English Literature. Government servant in Finance Department, Punjab since September 1993. Najamuddin Ahmed is a prolific fiction writer and novelist. He started his literary career many years ago by writing poetry. His poems were published in various prestigious journals. Later came to fictional prose and remained so. His fictional stories and translations continue to adorn the pages of respected Urdu journals. Along with fictional prose, he has also written some critical essays. So far, two collections of his short stories have been published which are as under: "Aao Bhai Khelain" (Thirteen Stories). First Edition 2013 "Farar aor Dosray Afsanay " (Seventeen Stories). First Edition 2017